Effect of Shifting Cultivation on Soil Microbial Biomass C, N and P under the Shifting Cultivations Systems of Kangchup Hills, Manipur, North- East India - P.S. Yadava, R. K. Binarani* and (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> ABSTRACT: The seasonal changes in the soil microbial biomass C, N and P have been carried out in four different shifting cultivation sites i.e., recently slashed and burnt site, 3-year old fallow site, 7-year old fallow site and a protected forest site. The soil microbial biomass C, N and P was found to be maximum in protected forest site followed by 7-year old fallow site, 3-year old fallow site and minimum in recently slash and burnt site. Seasonally microbial biomass C, N and P were highest during rainy season and lowest during winter in all the four study sites. A significant positive correlation was observed between the microbial biomass C, N and P with abiotic factors, such as, soil moisture, soil temperature and soil organic carbon in all the four study sites. Thereby it shows that soil temperature, soil moisture and organic carbon influences the microbial biomass C, N and P.